Investigation the Dynamics of Learning Obstacles in Jumlah Ismiyyah Among Junior High School Students - Aulia, Robithah; Abdurrahman, Maman; Nurmala, Mia (Paedagogia: Jurnal Pendidikan, 2025)
Qawāʻid al-lugah al-‘arabiyyah in its complexity, continues to challenge learners, especially within jumlah ismiyyah. This research aims to identify these learning obstacles more deeply using Brosseau's learning obstacle framework. Learning obstacles are categorized into three types based on their causes: ontogenic, epistemological, and didactical obstacles. Ontogenic obstacles are further subdivided into psychological ontogenic obstacles, instrumental ontogenic obstacles, and conceptual ontogenic obstacles. This study employed a qualitative approach with a case study method. Purposive sampling was used as the sampling technique. Data were collected through observation, interviews, and document analysis. Findings reveal that students face ontogenic obstacles due to limited cognitive readiness, low motivation, and weak foundational understanding often reflected in errors identifying sentence components. Epistemological obstacles are marked by difficulties in applying grammatical concepts, such as recognizing jumlah ismiyyah across varied sentence structures. Didactical obstacles arise due to insufficient explanation of sentence transformation and lack of varied media and practice. These obstacles are influenced by multiple factors, including classroom conditions, student workload, cognitive preparedness, scheduling, instructional media, and teaching approaches. Among the three categories, epistemological obstacles are the most prominent, indicating a gap in conceptual comprehension. Identifying these learning obstacles is essential to designing more adaptive and effective instruction, ensuring students can progress toward deeper understanding in subsequent material.